2001
DOI: 10.2337/diabetes.50.2.348
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Increase in Plasma Leptin Markedly Inhibits Insulin Secretion In Vivo

Abstract: The demonstration of leptin receptors on the pancreatic ␤-cells suggests the possibility of direct actions of leptin on insulin secretion. In vitro studies on islets or perfused pancreas and ␤-cell lines produced inconsistent results. We performed an in vivo study to distinctly examine whether leptin has an effect on glucose-stimulated insulin secretion. Young chronically catheterized Sprague-Dawley rats (n = 28) were subjected to a 4-h hyperglycemic clamp study (~11 mmol/l). At minute 120 to 240, rats were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(75 citation statements)
references
References 37 publications
4
70
1
Order By: Relevance
“…35 Leptin receptors have been demonstrated on the β-pancreatic cell, 36 and in animal studies acute physiologic increases in leptin significantly inhibited glucose stimulated insulin secretion in a dose-dependent manner. 37 Plasma levels of leptin, adequate to significantly suppress insulin, are found in mild obesity 38 and patients with IGT. 39 Furthermore, leptin is associated with features of the metabolic syndrome such as IGT and controls nor between OSA patients with and without IGT.…”
Section: Neuropeptides and Impaired Glucose Tolerancementioning
confidence: 99%
“…35 Leptin receptors have been demonstrated on the β-pancreatic cell, 36 and in animal studies acute physiologic increases in leptin significantly inhibited glucose stimulated insulin secretion in a dose-dependent manner. 37 Plasma levels of leptin, adequate to significantly suppress insulin, are found in mild obesity 38 and patients with IGT. 39 Furthermore, leptin is associated with features of the metabolic syndrome such as IGT and controls nor between OSA patients with and without IGT.…”
Section: Neuropeptides and Impaired Glucose Tolerancementioning
confidence: 99%
“…Thus, O'Doherty et al (42) demonstrated that an acute infusion of leptin does not increase PDE3B activity in rat liver. Furthermore, Cases et al (43) determined that leptin suppression of insulin secretion in vivo is not blocked by milrinone, a PDE3B inhibitor. However, it should be noted that inhibition of PDE3B in the hypothalamus suppresses the effects of leptin on food intake (25), suggesting that a requirement for PDE3B activity for leptin action may be process-and tissue-specific.…”
Section: Figmentioning
confidence: 99%
“…13,14 Physiological increase in plasma leptin has been shown to significantly inhibit glucose-stimulated insulin secretion in vivo and to determine insulin resistance. 15 Plasma leptin concentration usually reflects the total amount of fat present in the body, and lower plasma leptin levels have been reported consistently among weight-losing patients. 16,17 The results of our study show that significant reduction of leptin levels occur early after gastric bypass when BMI is still in the morbidly obese range.…”
Section: The Role Of Leptinmentioning
confidence: 99%